Perceptions, attitudes, and subjective norms influencing seniors' decision to accept or reject mobility aids in fall prevention: An application of the theory of planned behavior. - Aminzadeh, Faranak. (University of Ottawa (Canada), 1997)
Many risk factors for falls among seniors are modifiable with appropriate interventions. Educational strategies to improve the use of mobility aids have been an important component of some fall prevention programs. However, literature and clinical observations point to poor acceptance of these devices by seniors. Guided by the Theory of Planned Behavior (TPB), this study was an exploratory investigation of attitudinal, normative, and perceptual determinants of cane use among community-residing older adults. The objectives were: (1) to develop valid and reliable measures of TPB constructs as they relate to the use of canes in fall prevention; (2) to determine relationships between various components of the model and cane use behaviors in a sample of community-dwelling older adults aged 65 and over; and, (3) to examine the differences between "cane-users" and "non-users" with respect to the TPB variables and selected sociodemographic and health-related characteristics. This descriptive comparative study involved two phases: (1) instrument development and pilot testing on a purposive sample of 10 seniors; and, (2) a cross-sectional survey of a convenience sample of 98 community-dwelling seniors in Ottawa-Carleton. Subjects were recruited from a variety of community settings, using both direct and indirect approaches. Data were collected through self- and interviewer-administered techniques. The findings provided some evidence for the validity and reliability of the instrument and confirmed the utility of the TPB in its application to a new domain of behavior. "Cane-users" were significantly older, reported greater mobility difficulties, and had more negative evaluations of their activity level compared to "non-users". However, the two groups did not significantly differ with respect to other sociodemographic characteristics, fall history and frequency, and self-rated health. There were significant differences between "cane-users" and "non-users" on all components of the TPB model, even after stratifying the sample by age and mobility level. (Abstract shortened by UMI.)
Keywords: Gerontology.